The striker - Huang, Ana (Huang, Ana. Gods of the game, 2024)
"She's the only woman he wants...and the only one he can't have. Asher Donovan is a living legend--the darling of the Premier League, the (arguably) greatest footballer in the world. But his reckless antics and recent team transfer have caused much controversy, and when his feud with his rival-turned-teammate costs them a championship, they're forced to "bond" during off-season cross-training. Surviving the summer shouldn't be hard...until Asher meets their new trainer. She's beautiful, talented, and no matter how hard he tries, he can't take his mind off her. The only problem? She's his rival's sister--and completely off limits. Scarlett DuBois is a former prima ballerina whose career was cut short by a tragic accident. Now a teacher at a prestigious dance academy but still haunted by the ghosts of her past, the last thing she wants is to spend the summer cross-training Asher Donovan, of all people. She swore she would never date a footballer, but when her brother leaves town for an emergency, she finds herself thrown into dangerously close proximity with the gorgeous, charming striker. Training, she can deal with. But falling in love? That's out of the question--especially when he's the only person with the power to break her heart"--